THE EFFECT OF COMPANY'S ROA AND SIZE ON ZAKAT IN SHARIA COMMERCIAL BANKS - Diaz Martha Chairunnisa; Anny Widiasmara (International Conference on Social and Islamic Studies, 2021)
The economy in Indonesia is growing rapidly, including the increasing bankingsector. Sharia banking must fulfill all economic orders that have been set out in the Qur'anand Hadith including obeying the pillars of faith and the pillars of Islam. One of the fivepillars of Islam that must be implemented is Zakat. According to Islamic law, zakat is anasset that is issued when it has reached the conditions stipulated in religious rules. So thatwith Zakat it will foster noble character for both muzzaki and mustahiq to uphold the Islamiceconomy with the grace of Allah Subhanallahu wata'ala. The purpose of this study is toprovide empirical evidence that ROA and firm size have an effect on Zakat. This research isquantitative, secondary data using annual financial report data at www.idx.co.id and thecompany's official website. The sample of Islamic Commercial Bank Companies is 13Islamic Commercial Banks in 2014-2020 using profitability Return on Assets (ROA) andcompany size as measured by Ln total assets. This study uses the data testing method used isdescriptive statistical analysis, hypothesis testing with SPSS 25 with multiple linearregression data analysis techniques and t test. The results showed that ROA and firm size hada significant effect on corporate zakat.